The effect of blended instruction on accelerated learning. Issue 3 (26th May 2016) - Patchan, Melissa M.; Schunn, Christian D.; Sieg, Wilfried; McLaughlin, Dawn
Abstract : While online instructional technologies are becoming more popular in higher education, educators' opinions about online learning tend to be generally negative. Furthermore, many studies have failed to systematically examine the features that distinguish one instructional mode from another, which weakens possible explanations for why online instructional technology can be beneficial. The current study isolates three benefits of the authors' particular online instructional technology: (1) providing flexibility in how students learn, (2) offering immediate and targeted feedback and (3) increasing student participation and engagement with instructional material. Maximum benefits were observed when students used the online instructional technology to prepare for their face-to-face class – that is, students with this blended instruction learned twice as much content in the same amount of time in comparison to students with face-to-face instruction alone, without creating an atypically high workload.